(untitled) (قضايا سياسية, 2023)
Poverty , Inequality & Terrorism Dr. Farah Dheia _ PhD. Political Sciences / Political System My research speak about three field , poverty , inequality & terrorism . When began to explain the poverty must show it causes & all figures many peoples suffering from them . Then Inequality related with poverty & terrorism , when peoples feeling Inequality that must led them to terrorism . The results of this words , terrorism happening by to clear causes & most power to push any people suffering from many problems like poverty & Inequality led them to Terrorism . My Report contain Three parts : Introduction Part One : Terrorism Part Two : Poverty Part Three : Inequality Conclusion Reference FARAH DHIAA ALSAFAR PH.D.POLITICAL SCIENCES